KONSTRUKSI SOSIAL BUDAYA ORIMOI MASYARAKAT SUKU TABARU DI DESA TOLISAOR KECAMATAN IBU UTARA KABUPATEN HALMAHERA BARAT - Piga, Herlan (Universitas Sam Ratulangi, 2015)
Orimoi is a cult of muteral helping among peoples, The Character of this is the description of the character of man of Tabaru, it is the leader of people in a bigger group and related to the activity of Orimoi. Everi Ngone (torang semua) of west Helmahera people look at the presentness of themselves in the Orimoi instituon as an honor, and the new number highly feels happy and honorable to carry out the responsibility together (annonimos)In the Orimoi, the ctructural organization can not be seen, since there is only one line of command which as to be heard by every members. It is title of the group of peoples that has been given to the adult man, even more exactly the heard master of old man, who is health, strong, smart prudent and has an influence in the peoples when he is to be domicile, even to the other people outside.The title to give without the process of election and it is never dispossessed on even in hrited. Basicl the title to be given because there is a merit to be very useful for the interest of people in general, in particular the peoples that can enjoy it. The leader. The leader of Orimoi group is only a command to coordinate all the activity of group so that the authorization of a leader has to be seen that he is to be eversed in his group, and also to the other group. Working continuously from the farmland owned by the members of one group, is a rule for the system of Orimoi group. The number of workers and working hours has to be same for all the group to cultivated the land of every member of the group Orimoi When there is amember of group cannot work (because of sick or other prevention), then, te leader has to be prudent to manage it. According to the tradition, the worker cannot work can be substited by the other worker (but from family him self or a member of the group), It is a primary chance before entering in to she working group it self.Orimoi is a value in heritance is very known by the peoples with is primary activity in farming sector and it still grows the primary principle of cooperation in farm cultivation is the highest spirit of working to rise the farming production; this fundamental principle is very known by all the members of Orimoi.In its application the cult of Orimoi is tobe tool of guide for the productive working spirit and working in togetherness. Orimoi cult or working together and help each other had is roots and being culture in the community custom of Tabaru. The Solidarity principle described in Orimoi culture and reflected in economic activities in the peoples of Tabaru tribe, in particular, in the peoples of Tolisaor Village, District of North Ibu West Halmahera Regency.Keywords : socio cultural, orimoi, solidarity